Regulation (EU) 2017/2226 of the European Parliament and of the Council of 30 November 2017 establishing an Entry/Exit System (EES) versus data protection – Is it done in the right way? - Wojnowska-Radzińska, Julia (Review of European and Comparative Law, 2019)
The purpose of this paper is to explore whether the processing of personal data under Regulation 2017/226 is compatible with the principle of proportionality in the light of Charter of Fundamental Rights of the EU and the case-law of the Court of Justice of the European Union (CJEU). The Regulation 2017/2226 provides the EES system which is the only system that collects the entry/exit data of all third-country nationals entering the Schengen area for a short stay, whether via a land, sea or air border. The EES replaces the current system of manual stamping of passports.